Black Orchid - Gaiman, Neil (DC comics/Vertigo, 2012)
A plant/human hybrid superhero called Black Orchid goes on a spiritual journey in the wake of her death, during which she reviews her life, investigates her origins, and is given the opportunity to avenge herself.